Reconceptualizing social indicators in the Caribbean : a review and discussion (UN ECLAC Port of SpainTT, 2000)
Reviews social indicators which are presently used in the Caribbean for collection of data published on social development. Discusses some of the issues critical to the use of social indicators in general. Focuses on the relevance and limitations of selected social indicators from the Caribbean and identifies some of the problems which exist when attempting to analyze data from the Caribbean. Looks at issues related to existing social data and concerns about quality and availability of such data for purposes of social planning and implementation of required programmes and projects.
Keywords: SOCIAL INDICATORS